Agri-food System Transformation and Policy and Investment Prioritization in Odisha - CGIAR (CGIAR System Organization, 2023)
IFPRI researchers Dr. Karl Pauw, Senior Research Fellow, and Dr. Barun Deb Pal, Research Coordinator, met up with officials from the Government of Odisha on 21st November 2022 at Krushi Bhawan to discuss the 2023 work plan for Odisha state under CGIAR Initiative on National Policies and Strategies (NPS) activity. The meeting was chaired by Sri S.K. Chadha, IFS, Special Secretary to Government, Department of Agriculture & Farmers’ Empowerment, Odisha. The discussion was to take forward the activities post IFPRI’s MoU with Govt of Odisha in May 2022.